Implementasi Forgiveness Therapy untuk Meningkatkan Pertumbuhan Pribadi Warga Binaan Lembaga Pemasyarakatan Perempuan Kelas II-A Tangerang - Azimah Syahidah; Putri Dian Dia Conia; Puspa Pertiwi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2026)
This study aims to examine the effectiveness of implementing forgiveness therapy in enhancing the personal growth of inmates at the Tangerang Class II-A Women’s Correctional Facility. The method used was a pre-experimental study with a one-group pretest-posttest design. Nine subjects aged 20-40 years were selected from 50 inmates based on low to moderate scores on the forgiveness scale and the psychological well-being scale. The intervention consisted of six sessions adapted from the forgiveness model developed by Enright and Fitzgibbons. Data analysis utilized a paired-sample t-test and the N-Gain formula. The results showed a significant increase in personal growth scores from the pretest (M = 7.00; SD = 1.225) to the posttest (M = 9.44; SD = 1.424), with t(8) = −8.315 and p < 0.001. An N-Gain value of 0.610 indicates moderate effectiveness. The follow-up measurement (M = 9.67; SD = 1.118) did not differ significantly from the post-test (p = 0.347), indicating the sustainability of the changes achieved. Forgiveness scores also increased from 65.33 (pre-test) to 86.67 (post-test) and 87.33 (follow-up), confirming the role of forgiveness as a psychological mechanism for personal growth. These findings support the integration of structured forgiveness therapy into correctional programs for women’s prisons.